(untitled) (E Conference Zone, 2024)
The article reports the research in the field of studying the mechanism of action of bio stimulators is currently quite relevant. A significant increase in B-lymphocytes in the blood of animals when using tissue bio preparations may indicate the activation and proliferation of cells in the humoral arm of the immune system in the experimental groups of animals.